Effects of tetrandrine on rabbit platelet aggregation and platelet activating factor generation - ZHANG Min; ZHANG le-zhi; LU Jin-sheng (Acta Pharmacologica Sinica; Vol 16, No 3 (May 1995): Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of tetrandrine (Tet) on platelet aggregation and platelet activating factor (PAF) generation in rabbit platelet-rich plasma (PRP). METHODS: The aggregation rate of platelets induced by calcimycin (Cal) and PAF and the inhibition rate of Tet on platelet aggregation were measured. The amount of PAF in PRP stimulated with Cal and treated with Tet was also measured. RESULTS: Cal 1-8 mumol.L(-1) and PAF 9.5-190.5 pmol.L(-1) induced platelet aggregation. At the final concentrations of 4-64 mumol.L(-1), Tet inhibited the aggregation induced by Cal 4 mumol.L(-1) and PAF 142.9 pmol.L-1. The IC50 (95% confidence limits) were 8.6 (6.0-12.2) mumol.L-1 for Cal and 14.0 (6.4-30.4) mumol.L(-1) for PAF. In the PRP aggregation by Cal, there was a marked increase in PAF content. Tet dependented the release of PAF from platelets by Cal in a concentration-dependent manner, with IC50 of 21 (8-54) mumol.L(-1). CONCLUSION: The inhibition effect of Tet on platelet aggregation might be concerned with the reduction of endogenous PAF generation.